Association of nephrotoxicity during platinum-etoposide doublet therapy with UGT1A1 polymorphisms in small cell lung cancer patients. (December 2018) - Anai, Satoshi; Iwama, Eiji; Yoneshima, Yasuto; Otsubo, Kohei; Tanaka, Kentaro; Nakanishi, Yoichi; Okamoto, Isamu
Highlights: Platinum-etoposide toxicity was associated with UGT1A1 polymorphisms in SCLC patients. Etoposide-induced nephrotoxicity was significantly associated with such polymorphisms. Reduced etoposide glucuronidation activity of UGT1A1 variants may cause nephrotoxicity. Abstract: Objectives: Etoposide is a key agent in the treatment of small cell lung cancer (SCLC). Uridine diphosphate (UDP)–glucuronosyltransferase 1A1 (UGT1A1) is thought to be largely responsible for the glucuronidation of etoposide as well as that of irinotecan, suggesting that polymorphisms of UGT1A1 might be predictive of etoposide toxicity. We therefore examined the relation between UGT1A1 polymorphisms and toxicity profile during platinum-etoposide doublet therapy in SCLC patients. Materials and Methods: SCLC patients who underwent platinum-etoposide doublet therapy and molecular testing for UGT1A1 genotype were reviewed for the occurrence of adverse events during treatment. Results: A total of 41 SCLC patients received platinum-etoposide doublet therapy and were genotyped for UGT1A1*6 and UGT1A1*28 alleles. These alleles were detected in 15 (36.6%) patients, with the genotypes of *6/–, *6/*6, *28/–, *28/*28, or *6/*28 being observed in 9 (22.0%), 2 (4.9%), 2 (4.9%), 1 (2.4%), and 1 (2.4%) patients, respectively. The presence of these alleles was significantly associated with an increase in serum creatinine concentration of grade ≥2 (incidence of 66.7% for patients with the alleles versus 11.5% for those without, P  <  0.001). Multivariate analysis also showed that these UGT1A1 alleles were significantly associated with therapy-induced nephrotoxicity (odds ratio of 19.30, 95% confidence interval of 2.50–149.00, P  <  0.005). Although the differences did not achieve statistical significance, the incidence of other severe toxicities including febrile neutropenia was also slightly higher in patients with the UGT1A1*6 or UGT1A1*28 alleles than in those without them. Conclusion: Our results reveal an association between UGT1A1 polymorphisms and toxicity of platinum-etoposide doublet therapy in SCLC patients, suggesting that close monitoring for toxicity, especially nephrotoxicity, is warranted for patients with such variant alleles receiving this treatment.